Rhetorical relations in multimodal documents. (February 2013) - Taboada, Maite; Habel, Christopher
We present a corpus-based study of coherence in multimodal documents. We concern ourselves with the types of relationships between graphs and tables and the text of the document in which they appear. In order to understand and categorize the types of relations across modalities, we are making use of Rhetorical Structure Theory (Mann and Thompson, 1988), and propose that this can adequately describe these types of relations. We analyzed a corpus comprising three different genres, and consisting of about 1500 pages of material and almost 600 figures, tables and graphs. We show that figures stand in both presentational and subject matter relations to the text, and that the relationship between figures and text is one of a small set out of the larger possible rhetorical relations. We also discuss several issues that arise in the treatment of multimodal material, such as the potential for multiple connections between figure and text.